Religion-Scientific Study of Solar Resting Phase and Solar-Lunar Finality: Solar Resting Phase and Solar-Lunar Finality - Adel, Miah Muhammad (AL-IKHSAN: Interdisciplinary Journal of Islamic Studies, 2023)
Religious views on the final state of the Sun, the Moon, the Final Hour, and the astrophysical findings of the solar and lunar fate have been reviewed. Religious views are that the Sun runs its course for a specified time, and it has a resting phase. Also, the advent of the Last Hour will be marked by the Sun’s overhead appearance causing tremendous heat, sunrise in the western sky, engulfing of the Moon, and ultimate vanishing. These religious forecasts were made in the 7th century. Scientists have found that the Sun has lived for 4.5 billion years and make forecast for living another 4.5 billion years. It passes through violent and quiet states every 11 years. The Sun’s red giant state will be large enough to spread beyond the orbit of the Earth by 20% and will be 3,000 times brighter. The Moon recedes away from us, and it will be lost in the Sun. After the red giant phase is over, the Sun will end up as a white dwarf with half of its mass. These astronomical discoveries were made in the early 20th century. Many discoveries could be made if the heavenly bodies’ Qur’anic highlights would be followed.